1996
DOI: 10.1016/s0092-8674(00)81988-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Intestinal Polyposis in ApcΔ716 Knockout Mice by Inhibition of Cyclooxygenase 2 (COX-2)

Abstract: Two cyclooxygenase isozymes catalyze conversion of arachidonic acid to prostaglandin H2: constitutive COX-1 and inducible COX-2. To assess the role of COX-2 in colorectal tumorigenisis, we determined the effects of COX-2 gene (Ptgs2) knockouts and a novel COX-2 inhibitor on Apc delta716 knockout mice, a model of human familial adenomatous polyposis. A Ptgs2 null mutation reduced the number and size of the intestinal polyps dramatically. Furthermore, treating Apc delta716 mice with a novel COX-2 inhibitor reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
1,336
5
24

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,131 publications
(1,421 citation statements)
references
References 33 publications
56
1,336
5
24
Order By: Relevance
“…The median number of COX-2-positive superficial stromal cells in colon carcinomas was 212.8/mm 2 (Table 1). There was neither association between the number of COX-2-positive superficial stromal cells and VEGF expression and microvessel density (P ¼ 0.29 and 0.81, respectively).…”
Section: Cox-2 Expressing Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of COX-2-positive superficial stromal cells in colon carcinomas was 212.8/mm 2 (Table 1). There was neither association between the number of COX-2-positive superficial stromal cells and VEGF expression and microvessel density (P ¼ 0.29 and 0.81, respectively).…”
Section: Cox-2 Expressing Stromal Cellsmentioning
confidence: 99%
“…In animal models, COX-2 knockout or treatment with specific COX-2 inhibitors reduces intestinal tumor development. [2][3][4][5] COX-2 tumor promotion probably involves different biological mechanisms, among them being the induction of tumor angiogenesis. 6 Indeed, COX-2 overexpression in colon cancer cells regulates angiogenesis in vitro and in vivo.…”
mentioning
confidence: 99%
“…Expression of both COX-2 and mPGES-1 is also induced in a variety of cancer tissues 8 . It is established that COX-2 plays a key role in gastrointestinal cancer development 9 , and inhibition of COX-2 in mouse models by selective inhibitors suppresses gastric and intestinal tumorigenesis 10,11 . Furthermore, PGE 2 is also implicated in gastrointestinal tumor development 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicate that Cox-2 is overexpressed in 85-90% of cancerous tissues from human colon and inhibition of Cox-2 by nonsteroidal anti-inflammatory drugs decreases the risk of colorectal cancer (revised by Gupta and Dubois, 2001;Chan, 2002). Experiments with Apc gene-deficient mice (Min mice) and Apc D716 /Cox-2 double-knockout mice revealed that either pharmacologic inhibition or genetic ablation of Cox-2 resulted in reduced intestinal tumorigenesis (Oshima et al, 1996;Williams et al, 1996). Enhanced synthesis of Cox-2-derived PGs may favor tumor growth by stimulating cell proliferation, promoting angiogenesis, inducing local immunosuppression, increasing invasiveness and inhibiting apoptosis (Kawai et al, 2002;Iniguez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%